2019
DOI: 10.3390/pr7080494
|View full text |Cite
|
Sign up to set email alerts
|

Economic Viability and Environmental Efficiency Analysis of Hydrogen Production Processes for the Decarbonization of Energy Systems

Abstract: The widespread penetration of hydrogen in mainstream energy systems requires hydrogen production processes to be economically competent and environmentally efficient. Hydrogen, if produced efficiently, can play a pivotal role in decarbonizing the global energy systems. Therefore, this study develops a framework which evaluates hydrogen production processes and quantifies deficiencies for improvement. The framework integrates slack-based data envelopment analysis (DEA), with fuzzy analytical hierarchy process (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…However, in this study, a fuzzy-based TOPSIS method has been employed to obtain more reliable results by minimizing the uncertainty of the decision problem. The fuzzy set theory helps in providing the incomplete information and immeasurable problem under fuzzy environment [69,70]. This method is preferable in evaluating and ranking the alternatives using linguistic variables.…”
Section: Fuzzy Technique For Order Of Preference By Similarity Ideal mentioning
confidence: 99%
“…However, in this study, a fuzzy-based TOPSIS method has been employed to obtain more reliable results by minimizing the uncertainty of the decision problem. The fuzzy set theory helps in providing the incomplete information and immeasurable problem under fuzzy environment [69,70]. This method is preferable in evaluating and ranking the alternatives using linguistic variables.…”
Section: Fuzzy Technique For Order Of Preference By Similarity Ideal mentioning
confidence: 99%
“…As discussed earlier, the selection of SEZ requires complex and meticulous consideration that should be based on an appropriate scientific decision framework. The numerous studies have utilized MCDA methods for complex decision problems, such as PROSA method [39,40], NEAT-F-PROMETHEE method [41], AHP [42], Fuzzy AHP [43][44][45], and Fuzzy Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) [46]. This study provides a comprehensive research framework comprised of AHP and a fuzzy VIKOR decision model as shown in Figure 3.…”
Section: Methodsmentioning
confidence: 99%
“…Ever since Hwang and Yoon proposed the TOPSIS method in 1981, the technique has been commonly used for solving complex decision problems [52]. Few of the recent studies that used TOPSIS include [50,53]. The TOPSIS method solves the problem by finding the positive and negative ideal solution.…”
Section: Topsismentioning
confidence: 99%